Focus in Corrective Exchanges: Effects of Pitch Accent and Syntactic Form. (December 2016) - Clifton, Charles; Frazier, Lyn
A dialog consisting of an utterance by one speaker and another speaker's correction of its content seems intuitively to be made more acceptable when the new information is pitch accented or otherwise focused, and when the utterance and correction have the same syntactic form. Three acceptability judgment studies, one written and two auditory, investigated the interaction of focus (manipulated by sentence position and, in Experiments 2 and 3, pitch accent) and syntactic parallelism. Experiment 1 indicated that syntactic parallelism interacted with position of the new (contrastive) term: nonparallel forms were relatively acceptable when the new term appeared in object position, a position that commonly contains new information (a 'default focus' position). Experiments 2 and 3 indicated that presence of a pitch accent and placement in a default focus position had additive effects on acceptability. Surprisingly, spoken dialogs in which the new term appeared in object position were acceptable even when given information carried the most prominent pitch accent. The present studies, and earlier work, suggest that corrected information can be focused either by prosody or position even in spoken English–a language often thought to express focus through pitch accent, not syntactic position.